2011
DOI: 10.1111/j.1365-3016.2010.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal reproductive history and the risk of isolated congenital malformations

Abstract: We examined the relationship between maternal reproductive history and the newborn's risk of isolated congenital malformations in a large case-control cohort from the Polish Registry of Congenital Malformations. Congenital malformations were classified into four categories: isolated congenital heart defects (n=1673), isolated cleft palate (n=255), cleft lip with or without cleft palate (n=448) and renal agenesis (n=103). The case groups were compared with a shared group of 2068 controls recruited in the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…All of the studies were published from 1989 to 2013. There were 31 case–control studies [15] , [20] [37] , [39] [41] , [43] [48] , [52] [54] and 2 cohort studies [38] , [42] . The main characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies were published from 1989 to 2013. There were 31 case–control studies [15] , [20] [37] , [39] [41] , [43] [48] , [52] [54] and 2 cohort studies [38] , [42] . The main characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 1. In all, 20 studies [16] , [23] [25] , [27] [33] , [35] , [38] , [39] , [42] [44] , [46] , [52] , [54] were conducted in the United States/Canada, 11 in Europe [20] [22] , [34] , [36] , [37] , [40] , [41] , [45] , [47] , [53] , and 2 in other regions (1 in China and 1 in Egypt) [26] , [35] ; 29 studies were conducted in high-income countries and 4 in middle or low-income countries. Of the studies examined, 29 investigated the association of educational attainment with CHD risk [16] , [20] , [21] , [23] [45] , [47] , [52] , [53] , 6 examined the association of family income level with CHD risk [23] , [24] , [29] , [31] , [39] , [54] , and 5 examined the association of occupational categories with CHD risk [22] , [34] , [44] , [46] , [48] .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the prevailing opinion in patients with a maternal history of RPL, which consisted of the other two-thirds of our study group, is that the RPL itself is a risk factor for birth defects of next pregnancies. 20 The transfer of IgG from mother to fetus begins from 12 weeks of GA. 18 The amount of transferred IgG increases with gestational age and sharply increases from late second trimester (28-32 weeks of GA). Finally at term, fetal IgG level exceeds the maternal one.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 describes the most frequent adverse obstetric outcomes or conditions and their association with the various descriptors, including maternal age, gravidity, parity, history of preterm delivery, history of abortions, race and ethnicity, and prepregnancy BMI. Of the 34 listed adverse obstetric outcomes or conditions, maternal age was linked to 20 (59%), [3][4][5][6][7][8][9][10][11][12][13][14][15] gravidity was linked to 11 (32%), 10,12,13,[16][17][18][19][20][21] parity was linked to 14 (41%), [10][11][12]14,18,19,22 history of preterm birth was linked to 18 (53%), 9,20,22,23 history of abortions was linked to 8 (24%), 17,19-21 and race and ethnicity were linked to 17 (50%). 15,[23][24][25][26][27] As shown in Table 3, BMI had the strongest association (32 [94%]) with adverse pregnancy outcomes or conditions.…”
Section: Methodsmentioning
confidence: 99%